Training in the UAE Context of Talent Management Initiatives: A Semi-Government Organisation Case Study - Al Suwaidi, Nawal Rashed (2014)
This dissertation examines the relationship between training and development and talent management (TM). The empirical research was supported by funding from the Federal Demographic Council, which had contracted the British University in Dubai to evaluate TM at micro and macro levels in all sectors of the UAE. This study focuses on a set of interviews with employees at different levels in the organisation, and aims to understand what TM means for them especially in semi-government companies. Training and Development is an essential component of many TM systems, and it has important roles in the development of UAE nationals and expatriates as well as having the potential to make a major contribution to semi-government organisations’ performance. The analysis of the interview data concentrates on difficulties associated with training, learning and development in the talent management context. It covers TM perspectives, support factors for training, learning and development (TLD), alignment with organisation strategy, TM challenges, training processes and solutions. The main findings from the interviews were difficulties experienced from the unwanted turnover of talent. In this case study organisation there were problems relating to: lack of processing and implementation of appropriate training, and a lack of management awareness of the importance of TLD. In addition, there were systemic problems relating to the majority of the business units not having specific budgets for TLD, partly due to it being stereotyped as wasteful of time, manpower and money. It is concluded that companies and the government should fully support TLD initiatives in the semi-government sector, and finally, recommendations are made to recruit and retain talented workers. Ways that companies can enhance talented employees’ work experience, knowledge, skills and competences are emphasised.